Foresight and Roadmapping Methodology: Trends and Outlook - Yusuke Kishita (Foresight and STI Governance, 2021)
This guest editorial article introduces contextual and theoretical frameworks of foresight and futures studies’ methodology.  Outstanding questions relating to methodological development are then addressed. This is followed by an introduction to five papers that make important methodological contributions. The article ends by a call for further research on the questions that have been identified, but remain unanswered.